Monitoring and Power Control on Solar Panels Based on the Internet of Things (IoT) - Binnerianto, Binnerianto; Ma’arif, Alfian; Iswanto, Iswanto (Association for Scientific Computing Electrical and Engineering (ASCEE), 2021)
Indonesia is a tropical country. Therefore, to utilize abundant solar energy, solar power plants or solar power are made. This research aims to make it easier to monitor the voltage of solar panels and batteries through the Blynk application and Google spreadsheets, as well as automatic power controllers. The tools used in this study are Arduino Uno, MCU ESP8266 node, voltage sensors, relays, solar charge controllers, inverters, batteries, and solar panels. The monitoring and power control tool in this study works at voltages of 12VDC, 5VDC, and 220VAC. Solar panel and battery voltage measurement results are automatically updated in the Blynk app and Google sheets. In the Blynk app the data is updated every 6 seconds, but in Google sheets the data is updated every 1 minute. The average voltage sensor readings per day of solar panels and batteries are 13.011V and 12.969V, with the average error percentage of solar panel voltage is 0.13875% and on batteries is 0.0059%.